2018
DOI: 10.1186/s12966-018-0718-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the acceptability and feasibility of reducing occupational sitting: review and thematic synthesis

Abstract: BackgroundReducing workplace sedentary behaviour (sitting) is a topic of contemporary public health and occupational health interest. Understanding workers’ perspectives on the feasibility and acceptability of strategies, and barriers and facilitators to reducing workplace sitting time, can help inform the design and implementation of targeted interventions. The aim of this qualitative synthesis was to identify and synthesise the evidence on factors perceived to influence the acceptability and feasibility of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 54 publications
18
43
0
Order By: Relevance
“…Together, the findings of the present study are in line with findings from other evaluations of sitting time interventions, and highlight the importance of an organizational perspective (e.g. [11]): This implies that sitting time interventions should address the organizational context from intervention development, through to the implementation process in order to ensure the best possible effect on sitting time. This could be obtained by: a proper fit between intervention and the present conditions of the workplace; adequate matching of expectations towards ambassadors and between participants; addressing social norms about sitting and intervention activities; and sustained levels of management and social support.…”
Section: Mental Modelssupporting
confidence: 89%
See 3 more Smart Citations
“…Together, the findings of the present study are in line with findings from other evaluations of sitting time interventions, and highlight the importance of an organizational perspective (e.g. [11]): This implies that sitting time interventions should address the organizational context from intervention development, through to the implementation process in order to ensure the best possible effect on sitting time. This could be obtained by: a proper fit between intervention and the present conditions of the workplace; adequate matching of expectations towards ambassadors and between participants; addressing social norms about sitting and intervention activities; and sustained levels of management and social support.…”
Section: Mental Modelssupporting
confidence: 89%
“…Participants consistently emphasized the role of the managers, which is in line with several other studies of other occupational health interventions [8,23] and sitting time interventions specifically [21,24,25]. In their review, Hadgraft et al [11] found support from managers in the form of approval of intervention activities and leading by example to be key facilitators in reducing workplace sitting, and this has been further supported by more recent studies [26].…”
Section: Organization Of the Interventionsupporting
confidence: 60%
See 2 more Smart Citations
“…Seeing agents use a height-adjustable workstation in the standing position was a prominent trigger for agents to work in a standing position. Equally, low participant numbers meant that agents were often situated in teams of mainly desk-based agents, and similar to findings in traditional office workers [73,74] and call agents [75], social pressure to conform to seated work appeared to negatively influence agent's motivation to use the height-adjustable workstation in the standing position. Refining the recruitment strategy to increase agent participation and locate participants more proximally to one another appears important for increasing interpersonal support to use height-adjustable workstations in the standing position [33].…”
Section: Discussionmentioning
confidence: 61%